Pengaruh lama fermentasi terhadap karakteristik ekstrak pulp biji kakao (Theobroma cacao. L): The effect of fermentation period to characteristics extracts of cocoa seed pulp (Theobroma Cacao. L) - Palupi, Hapsari Titi; Laily Susanti (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2024)
Cocoa pulp is a layer of mucus covering the beans which mostly consists of water and a layer of nutritional components that are quite high, including sucrose, glucose, organic acids and fiber. The fermentation process is carried out to release the cocoa pulp to produce cocoa pulp extract. This research aims to determine the effect of fermentation period on the characteristics of cocoa pulp extract and syrup. The research design used was a randomized block design, with period fermentation treatment were 24-hour, 48-hour, 72-hour, 96-hour, and each treatment was repeated 4 times. The parameters observed in the cocoa pulp extract were antioxidant activity, pH, total acid, yield and organoleptic (color, aroma and taste), while the organoleptic properties of the syrup were only observed. The results showed that treatment of fermentation period had a significant effect on pH, total acid and yield, however, it did not have a significant effect on antioxidants. The fermentation period also has a significant effect on the color, flavor and taste of cocoa pulp extract and the of cocoa syrup.